Effect of biotic and abiotic factors on composition and foraging intensity of subterranean termites - Swidiq Mugerwa; Moses Nyangito; Denis Mpairwe; John Nderitu (African Journal of Environmental Economics and Management, 2019)
Elucidating the influence of ecological factors on composition and foraging intensity of subterranean termites is critical in development of sustainable termite management strategies. Our aim was therefore to analyze the effect of selected biotic and abiotic factors on composition and foraging intensity of termites. We used principal component and canonical correspondence analysis to select appropriate factors and to model relationships respectively. MACROTERMES species occurred in sites where the quantity of litter was generally above the mean. However, MACROTERMES HERUS (Rambur) and MACROTERMES spp.4 occurred in sites where the litter quantity was below the mean. TRINERVITERMES OECONOMOUS (Tragardh) and ODONTOREMES spp.1 were noted to occur in the direction of increasing quantity of biomass. Generally, most species occurred in sites where soil pH was above or slightly below the mean (4.8). Majority of the species were also noted to occur in sites where bulk density was below or slightly above the mean (1.55 g/cm3). Highest bait consumption (95%) occurred within a range of 55 to 60% basal cover beyond which the amount of bait consumed reduced. Litter and biomass quantity, pH and bulk density were noted as the most influential environmental variables determining composition of termites while basal cover was the major determinant of foraging intensity.